Negative interest rates and the signalling channel - Kerstin Bernoth; Alexander Haas (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
While negative interest rates stimulate the real economy by enhancing credit supply and improving the wealth situation of firms and households, they might come with side effects with regard to banking and financial stability. In an assessment of the trade-off between the ability of a central bank to use negative policy rates to signal lower future deposits rates, against the potential costs on bank profitability, we find that the signalling effect dominates. Thus, a negative interest rate policy is an effective monetary policy tool, even when deposit rates are bound by zero.
Keywords: 330